The Impact of Multiple Rounds of Indoor Residual Spraying on Malaria Incidence and Hemoglobin Levels in a High-Transmission Setting - Zinszer, Kate (J Infect Dis, 2020)
BACKGROUND: Indoor residual spraying (IRS) is widely used as a vector control measure, although there are conflicting findings of its effectiveness in reducing malaria incidence. The objective of this study was to estimate the effect of multiple IRS rounds on malaria incidence and hemoglobin levels in a cohort of children in rural southeastern Uganda. METHODS: The study was based upon a dynamic cohort of children aged 0.5–10 years enrolled from August 2011 to June 2017 in Nagongera Subcounty. Confirmed malaria infections and hemoglobin levels were recorded over time for each participant. After each of 4 rounds of IRS, malaria incidence, hemoglobin levels, and parasite density were evaluated and compared with pre-IRS levels. Analyses were carried out at the participant level while accounting for repeated measures and clustering by household. RESULTS: Incidence rate ratios comparing post-IRS to pre-IRS incidence rates for age groups 0–3, 3–5, and 5–11 were 0.108 (95% confidence interval [CI], .078–.149), 0.173 (95% CI, .136–.222), and 0.226 (95% CI, .187–.274), respectively. The mean hemoglobin levels significantly increased from 11.01 (pre-IRS) to 12.18 g/dL (post-IRS). CONCLUSIONS: Our study supports the policy recommendation of IRS usage in a stable and perennial transmission area to rapidly reduce malaria transmission.